Innovative antenna designs : Performance and application diversity - Asan, Noor Badariah (Penerbit UTeM Press, 2025)
Advanced antenna and propagation technology will play a crucial role in transforming the way we live, work, and engage with our environment in order to catch up with the developing technologies. The choice of an antenna system for a specific application will also be a critical component of all nodes and devices and will present several design challenges such as purpose, shape, and placement. In this edited book, the authors bring new approaches for exploiting challenging propagation channels and the development of efficient, cost-effective, scalable, and reliable antenna and other related systems. Various current state-of-the-art technologies have been discussed and future perspectives have been highlighted. The book is aimed at a wide audience of industry and academic researchers, scientists, and engineers as well as advanced students in the field of antenna, propagation, and related topics. The audience can also use the discussed topics to better understand the effects of the technology on the current market and future developments of advanced communication systems.